UNDERSTANDING BRAND EXPERIENCE, BRAND TRUSTAND BRAND LOVE IN RELATIONSHIP - Putra, Halim Dwi (International Journal of Psychosocial Rehabilitation, 2020)
this paper goal at analyzing a model Brand experience, brand trust and brand love within the use of cellular wallets in Indonesia in 2020 and as a part lookup disertation of the writer's dissertation for doctoral research at Brawijaya university. 460 people as respondents all through Indonesia the usage of the machin formula because the variety of respondents is now not recognized with certainty. The result this lookup exhibit that;Brand experience has a positive effect on brand trust, with a path coefficient value of 0.229 and significant, with a P- Values of 0.013 a significance level of 0.05.The finding of the study give new idea to marketing, in understanding and reasons the important of effect factor brand experience among using mobile wallet in Indonesia.Last and foremost a thank you to LPDP as a funder / sponsor of this reseach.